Pentingnya Keterampilan Kewirausahaan Dalam Pendidikan Anak Usia Dini (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Early childhood education has a crucial role in forming the basis of children's development. One aspect that is increasingly recognized as important in this education is the development of entrepreneurial skills. Although young children may not yet fully understand the concept of business, an introduction to the basic concepts of entrepreneurship can provide a strong foundation for their future development.What is the right way to build an entrepreneurial spirit for young children and what methods are appropriate to apply. Meanwhile, introducing and cultivating an entrepreneurial spirit cannot be done instantly with young children, and the role of parents here is very supportive in forming the character of an entrepreneur in the future. This research uses a qualitative approach with descriptive explanatory analytical studies, this method illustrates the importance of building an entrepreneurial spirit for young children. The aim of this research is to examine the benefits of building an entrepreneurial spirit in young children through the development of informal education and this research is only limited to cultivating an entrepreneurial spirit in the family and their immediate environment. Through entrepreneurship training for children from an early age, the aim is to foster self-confidence, independence and become people who have high creativity so that they become more productive when they grow up. Informal education is very influential in developing attitudes and character to become an entrepreneur.The problem found was a lack of awareness about the importance of entrepreneurial awareness. The subject was conducted with early childhood education teachers. Surveys will be conducted on teachers in various early childhood education institutions to evaluate their understanding of entrepreneurial skills and how they integrate them in daily learning. Results of Increasing Children's Creativity: Measuring the increase in children's creativity levels through the introduction of entrepreneurial concepts in learning activities. Implementation of project-based learning, Integrating entrepreneurial concepts in project activities to increase children's involvement in the learning process.